Impact of a Review of a Smart Infusion Pump Library in Hematology/Oncology: Tailoring Content to Meet Specialty Needs. Issue 3 (10th April 2022) - Misko, Jeanie; Rawlins, Matthew; Ridley, Breigh
Abstract : Objectives: Errors involving chemotherapy or intravenous medications may cause serious patient harm. Dose error reduction software (DERS) for "smart" infusion pumps offers additional safety protection for their administration. Our institution uses DERS software hospital-wide; however, the hematology/oncology areas were noted to have reduced compliance with DERS recommendations. In response, we sought to review the DERS content and survey hematology/oncology end users' satisfaction with the software. Methods: A multidisciplinary working group was formed to review the current DERS entries for medications, fluids, and blood products. The review included details such as dose, rate, and concentrations. Dose error reduction software compliance was determined using vendor-supplied Continuous Quality Improvement software. An electronic survey assessing clinicians' satisfaction with the current DERS library and any challenges in its use was conducted before and after the review. Results: Ninety-one changes were made to 71 medications by the working group. Compliance with the DERS library went from 81.5% before the review to 87.3% after the review ( P = 0.257). Fifty-eight survey responses were received (30 prereview and 28 postreview) with improvements in staff satisfaction with the DERS library (83.3%–92.8%, P < 0.05). Near-miss events changed after the review from 2 to 0, and the number of alerts caused by values outside the DERS library reduced from 8788 before the review to 3383 after the review ( P ≤ 0.05). Conclusions: Review of a hematology/oncology DERS library found improvements that better met the needs of end users. Engagement with relevant stakeholders, in conjunction with ongoing communication and review, is required to improve compliance and satisfaction with DERS.